Comparison of institutional dynamics of regional development publishing and printing activities in Ukraine: Methodological and practical aspects - Volodymyr Bazyliuk; Andriy Shtangret; Oleksandr Sylkin; Iryna Bezpalko (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The study of the impact of institutions on the economy necessitates the assessment of such impacts and the definition of a clear list of methods and criteria for evaluation. The purpose of our research is the formation of a methodological approach that would allow to compare the institutional dynamics of the regional development of publishing and printing activities. In the process of scientific research, the method of modified gravity modeling was used. The objective of the study is the publishing and printing activity and the assessment of its development. Information base of research on the main results of the publishing and printing activities in three regions - Kyiv (city), Kharkiv and Lviv regions. The study period is 4 years. Economic and mathematical calculations according to the method of comparing the institutional dynamics of the regional development of the PPA presented in this paper are based on the method of modified gravity modeling. Were obtained data on the institutional distance between the leading regions of publishing and printing activities, confirming the conclusions about the presence of significant disparities in the development of activities. The methodological approach to comparing the institutional dynamics of regional development activities (based on a modified gravity model) will allow to assess the impact of basic institutions on the regional development of PPA and the possibility of a quantitative comparison of such effects. The presented approach is based on the concept of institutional distance between points in the space of indices of institutional development of activities in the two regions under consideration.
Keywords: E02; O11; L82; R10; 650; institutional environment; region; publishing; printing; publishing and printing activity; development and modified gravity model